Pilot fecal DNA barcoding in selected fruit bats in Davao City, Philippines - Bacus, Michael G.; Burgos Sammer C.; Elizagaque, Hannah G.; Malbog, Kameela Monique A.; Reponte, Mae A.; Gamalo, Lief Erikson D.; Achondo, Marion John Michael M.; Murao, Lyre Anni E. (Vol. 150, No.2 (April 2021), pages 531-[541].)
"The "Species from Feces" DNA barcoding offers new opportunities to study the challenging taxonomy and systematics of Philippine bats using a minimally-invasive strategy that employs a short 200-bp mitochondrial encoded cytochrome c oxidase I (mt COI) sequence. A pilot application of the technique to five species of fruit bats collected from Davao City, Philippines revealed accurate species identification and the extended ability to assess genetic diversity and evolutionary relationships. The 95-100% sequence identity matched with the field identification of bats, including the endemic Ptenochirus jagori, although only 62%of the sample could be sequenced"-title page.